Post-independence disillusionment, paranoia, and xenophobic violence in Susan Kiguli’s selected poems - Abdullahi, Nafiu; Ali Termizi, Arbaayah; Kaur, Hardev; Mohd Amin, Hasyimah (UPM Press, 2022)
This paper investigates xenophobia in selected poems by Susan Kiguli using psychoanalytic theory in post-independence Uganda. In order to explore the issue of xenophobia in Kiguli's selected poems, the study identified and analyzed three poems from the collection titled Home Floats in the Distance (2012). This was done in order to analyze the issue of xenophobia in Uganda, which has been identified as a post-independence disillusionment. As a direct consequence of this disillusionment, the people have gotten frustrated, and as a result, they have focused their rage on the defenseless immigrants who are now residing in the country. The notion of "institutionalized xenophobia" was also investigated as part of the study, as past governments are culpable of the heinous act. The study that was carried out analyzed Kiguli's portrayal of xenophobia in the poems that are being examined for this study through the lens of Melanie Klein's concept of the paranoid-schizoid position. This was done in order to better understand the scope of the problem. The current study has concluded that the issue of xenophobia is psychologically motivated rather than economic as put forward by the previous studies. The study looked into the issue of xenophobia as a post-independence issue in Uganda during military rule.